2017
DOI: 10.1007/s11356-017-8462-2
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review

Abstract: Arsenic (As) is a toxic metalloid. Serious concerns have been raised in literature owing to its potential toxicity towards living beings. The metalloid causes various water- and food-borne diseases. Among food crops, rice contains the highest concentrations of As. Consuming As-contaminated rice results in serious health issues. Arsenic concentration in rice is governed by various factors in the rhizosphere such as availability and concentration of various mineral nutrients (iron, phosphate, sulfur and silicon)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(48 citation statements)
references
References 185 publications
1
46
0
1
Order By: Relevance
“…The findings help in hypothesizing that both the genotypes and environmental factors play very important roles to control arsenic accumulation in rice grains [65]. The major factors that influence the arsenic accumulation in rice grain include the type of the rice cultivar, plant physiology, the place where the plant was cultivated, and the method of processing of rice [10]. It was found that concentration of arsenic in brown rice was higher than white rice [10].…”
Section: Accumulation Of Arsenic In Rice Grainmentioning
confidence: 91%
See 4 more Smart Citations
“…The findings help in hypothesizing that both the genotypes and environmental factors play very important roles to control arsenic accumulation in rice grains [65]. The major factors that influence the arsenic accumulation in rice grain include the type of the rice cultivar, plant physiology, the place where the plant was cultivated, and the method of processing of rice [10]. It was found that concentration of arsenic in brown rice was higher than white rice [10].…”
Section: Accumulation Of Arsenic In Rice Grainmentioning
confidence: 91%
“…The major factors that influence the arsenic accumulation in rice grain include the type of the rice cultivar, plant physiology, the place where the plant was cultivated, and the method of processing of rice [10]. It was found that concentration of arsenic in brown rice was higher than white rice [10].…”
Section: Accumulation Of Arsenic In Rice Grainmentioning
confidence: 99%
See 3 more Smart Citations